2020
DOI: 10.1088/1674-1056/aba60f
|View full text |Cite
|
Sign up to set email alerts
|

A novel method of constructing high-dimensional digital chaotic systems on finite-state automata*

Abstract: When chaotic systems are implemented on finite precision machines, it will lead to the problem of dynamical degradation. Aiming at this problem, most previous related works have been proposed to improve the dynamical degradation of low-dimensional chaotic maps. This paper presents a novel method to construct high-dimensional digital chaotic systems in the domain of finite computing precision. The model is proposed by coupling a high-dimensional digital system with a continuous chaotic system. A rigorous proof … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…In addition, the histogram variance can be used to measure the uniformity of a histogram. [58,59] The definition is as follows:…”
Section: Safety Analysis 51 Histogram Analysismentioning
confidence: 99%
“…In addition, the histogram variance can be used to measure the uniformity of a histogram. [58,59] The definition is as follows:…”
Section: Safety Analysis 51 Histogram Analysismentioning
confidence: 99%
“…3(c), only small parts of this system are in chaos. When the control parameter is within [5,18], the LE of the Lorenz map is positive, and the system is in chaos. In other regions, the LE jumps and changes randomly, which harms the practical application of chaos.…”
Section: Enhanced Lorenz Mapmentioning
confidence: 99%
“…[17] Secondly, chaos degradation may occur when chaotic behaviors are simulated in finite precision. Some extremely approached states may overlap and appear to be precision truncated, [18] which causes the chaotic behaviors that originally had infinite states to degrade to inevitable periodic behaviors. Thirdly, existing chaotic maps show chaotic behaviors only in limited regions.…”
Section: Introductionmentioning
confidence: 99%
“…Dissipative chaos widely exists in physical systems, such as Chua's circuit, [1] double pendulum, [2] ballistic Dirac fermion systems, [3] the Peyrard-Bishop-Dauxois DNA model, [4] and some artificial nonlinear systems. [5][6][7] In contrast to dissipative chaos, conservative chaos can only be found in some theoretical models in the fields of celestial mechanics, molecular dynamics and hydrodynamics, such as the Hénon-Heiles system describing the motion of a star in a cylindrically symmetric and gravitationally smooth galactic potential, [8] two coupled anharmonic oscillators associated with molecular dynamics, [9] coupled Bloch oscillator equations representing electronic excitations of molecular dimers, [10] and hydrodynamic pilotwave system. [11] So far, the existing results have shown that the conservative chaos can be generated by Hamiltonian systems [12,13] as well as thermostatted systems.…”
Section: Introductionmentioning
confidence: 99%